The frequency of Toxocara infection in mental retarded children - Kaplan, M; Kalkan, A; Hosoglu, S; Kuk, S; Özden, M; Demirdag, K; Ozdarendeli, A (Fundaco Oswaldo Cruz, 2004)
Human toxocariasis is commonly seen in places where stray and Toxocara canis-infected dog population is high. There is a strong correlation between frequency of Toxocara infection, life style, and infection risk. Institutionalization of mental retarded patients increases to risk of toxocariasis. In this study, we aimed at investigating the frequency of Toxocara infection among children with mental retardation not requiring institutionalization. The study included 96 cases, who had educatable mental retardation and 85 healthy subjects who comprised the control group. Anti-Toxocara IgG or IgM antibodies were investigated in all serum samples, using ELISA method. The frequency of Toxocara infection was found significantly higher in mental retarded cases than in those in the control group (18.8% and 7.1% respectively) (p < 0.05). There was no significant difference between mental retarded children and the control group in terms of mean age, age groups, gender, owning dogs and cats and duration of their ownership, socio-economic level and behavioural factors, and personal hygiene (p > 0.05). We did not find any significant difference between Toxocara seropositive and seronegative mental retarded children in terms of demographic factors and epidemiological factors that could increase the risk of Toxocara infection (p > 0.05). The present study is the first seroprevalence study carried out with a mental retarded group not requiring institutionalization. Determination of high frequency of Toxocara infection suggests that these subjects constitute a risk factor for Toxocara infection, which may be attributed to their behavioural patterns.
Keywords: mental retarded children; Toxocara canis; toxocariasis